Pengaruh Komitmen Organisasi Dan Motivasi Terhadap Kinerja Auditor Dengan Kecerdasan Emosional Sebagai Variabel Moderating Pada Inspektorat Provinsi Sumatera Utara - Nikmah Khairani (Universitas Islam Negeri Sumatera Utara, 2020)
The performance of the auditor or the quality of work performed by the auditor is the total work that has been received by the auditor in carrying out his duties within the work period of the auditor. Three things that affect the auditor's performance are individual factors contained in the auditor, work environment factors and psychological factors. The purpose of this study was to analyze the effect of organizational commitment and motivation on auditor performance with emotional intelligence as a moderating variable in the Inspectorate of the Province of North Sumatra. The study was conducted at the Inspectorate of North Sumatra Province. The population in this study were 104 auditors and the sample was obtained using the Slovin formula of 50 respondents. Analysis techniques that use moderated regresion analysis (MRA). The results were obtained: 1) Organizational commitment influences auditor performance, 2) Motivation influences auditor performance, 3) Organizational commitment and motivation influences auditor performance, 4) Emotional intelligence moderates the effect of organizational commitment on auditor performance, 5) Emotional intelligence moderates the effect of motivation on auditor performance.